2021
DOI: 10.1038/s41541-021-00393-6
|View full text |Cite
|
Sign up to set email alerts
|

Scientific rationale for developing potent RBD-based vaccines targeting COVID-19

Abstract: Vaccination of the global population against COVID-19 is a great scientific, logistical, and moral challenge. Despite the rapid development and authorization of several full-length Spike (S) protein vaccines, the global demand outweighs the current supply and there is a need for safe, potent, high-volume, affordable vaccines that can fill this gap, especially in low- and middle-income countries. Whether SARS-CoV-2 S-protein receptor-binding domain (RBD)-based vaccines could fill this gap has been debated, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
127
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 115 publications
2
127
0
Order By: Relevance
“…Among the 110 COVID-19 vaccine candidates in clinical trials, the largest number (37, 34%) are subunit preparations 5 . Approximately half (16/37) of these candidates use full-length spike protein, with the rest focused on RBD (mostly its monomeric form 9 ) or peptides 5 , 10 . Our research group consisting of a consortium of academic institutions including the International Center for Vaccinology at the Kazakh National Agrarian Research University (KazNARU) and the Aikimbayev National Research Center for Especially Dangerous Infections of the Ministry of Health of the Republic of Kazakhstan has been developing a protein subunit vaccine against COVID-19 called NARUVAX-C19 in collaboration with Australian biotechnology company, Vaxine Pty Ltd.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 110 COVID-19 vaccine candidates in clinical trials, the largest number (37, 34%) are subunit preparations 5 . Approximately half (16/37) of these candidates use full-length spike protein, with the rest focused on RBD (mostly its monomeric form 9 ) or peptides 5 , 10 . Our research group consisting of a consortium of academic institutions including the International Center for Vaccinology at the Kazakh National Agrarian Research University (KazNARU) and the Aikimbayev National Research Center for Especially Dangerous Infections of the Ministry of Health of the Republic of Kazakhstan has been developing a protein subunit vaccine against COVID-19 called NARUVAX-C19 in collaboration with Australian biotechnology company, Vaxine Pty Ltd.…”
Section: Discussionmentioning
confidence: 99%
“…The Omicron variant (BA.1 and BA.2 lineages) has over 50 new mutations, >15 of which are in the receptor-binding domain (RBD) of the Spike (S) protein ( 2, 3 ). Given that over 90% of neutralizing antibodies present in plasma of convalescent individuals and up to 99% of neutralizing antibodies elicited by vaccination with the mRNA-1273 vaccine are directed to the RBD ( 4 ), these mutations could be largely responsible for Omicron’s ability to evade neutralizing antibodies induced by the approved COVID-19 vaccines ( 58 ). Multiple studies have shown a 20-to 30-fold reduction in neutralization antibody activity against Omicron in the sera of primary vaccine recipients compared with the ancestral SARS-CoV-2 or D614G viruses ( 57,912 ).…”
Section: Main Textmentioning
confidence: 99%
“…While these vaccines demonstrated remarkable reduction in disease, there still remain urgent and unmet needs for the vaccine worldwide and development of new platform vaccines is needed to resolve cold chain supply issues, disparity of vaccination rate between countries, and emergence of variants. 2 In response to these challenges, SK Bioscience Co., Ltd. (Korea) has been focusing on developing synthetic protein-based vaccine candidates especially targeting RBD region as an antigen which has potential advantages on high production yield, thermostability, and focusing immunity on key protective determinants, anticipating that would help increase population immunity. 2 GBP510 is a recombinant protein vaccine that consists of self-assembling, two-component nanoparticles displaying the receptor-binding domain (RBD) of the SARS-CoV-2 Spike protein in a highly immunogenic array.…”
Section: Introductionmentioning
confidence: 99%